SEDATION AND LARYNGOSPASM IN PEDIATRIC SURGERY: A SYSTEMATIC REVIEW - Alves Bezerra Bezerra, Rebeca; Ester Silva Damasceno, Jullyanne; Ferreira de Farias, Natália; da Nóbrega Dias, Milena (Health and Society, 2024)
Introduction: The use of anesthetics in pediatrics is essential for diagnostic and therapeutic procedures. The incidence of post-anesthetic respiratory complications is often avoidable with appropriate intervention. Laryngospasm, a reflex obstruction of the vocal cords, is more common in children. Objective: To discuss respiratory complications, with an emphasis on laryngospasm, during the use of anesthetics in pediatric procedures. Method: The Medical Literature Analysis and Retrieval System Online (MEDLINE, via PUBMED), Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SciELO), and Virtual Health Library (VHL) databases were used. Seven articles were selected that met the systematic review criteria. Results: The incidence of laryngospasm is 0.87% in adults, 1.7% in children, and 2.82% in babies. In children, it occurs mainly during emergence from anesthesia. Risk factors include inadequate anesthesia, respiratory infections and multiple attempts at airway management. Drug combinations such as propofol, ketamine and fentanyl are used to minimize complications. Preventive measures include clearing secretions and adequate depth of anesthesia. Drugs such β2-adrenergic agonists, such as albuterol, are used to reduce respiratory resistance during intubation. Training strategies with low-cost simulators are effective for managing difficult airways in pediatrics. In pediatric surgery, the laryngeal mask is preferred to endotracheal intubation to reduce respiratory complications. Studies indicate that positive communication between anesthesia teams improves performance in critical situations. Conclusion: Laryngospasm is a serious complication in pediatric anesthesia, more common in children due to their anatomy and sensitive reflexes. Risk factors include respiratory infections, asthma, smoking, gastroesophageal reflux, and superficial anesthesia. Prevention involves the proper use of anesthetics, cleaning secretions and careful monitoring. Medications such as propofol, ketamine, and albuterol can reduce adverse effects. Simulator training and effective communication in anesthesia teams improve clinical performance. With proper management, most episodes are resolved without long-term complications.